Policies and Directions for Digital Development: Restructuring the Protection and Services of International Migrant Workers - Wahyono, Eko (Department of Sociology, Universitas Nasional (Indonesia), 2020)
Policy has an important position in the process of developing digital technology. Many stakeholders are involved in the process of developing digital technology for international migrant workers. The government and NGOs are considered as one of the parties who have a major role in the policy making process and implementation of policies related to the use of digital technology for international migrant workers. Migrant workers are considered as a group that is vulnerable to security while working abroad. The problems faced are related to the security and management of migrant worker services while abroad. The development of digital technology presents challenges and opportunities, especially in policies that support and provide services to international migrant workers. Policy restructuring and implementation at various policy levels is important for accelerating the implementation of digitizing the services of international migrant workers from Indonesia. Keywords : Policy, digital, services, migrant workers